1988
DOI: 10.1002/masy.19880150108
|View full text |Cite
|
Sign up to set email alerts
|

Applications and limitations of deuterium labeling methods to neutron scattering studies of polymers

Abstract: -Deuterium labeling techniques have been widely used to study polymer chain configuration and motion, based on the assumption that the H-and D-chains ar~thermodynamically identical and that the interaction parameter between them, XlID is zero. By an appropriate choice of the degree of polymerization and temperature, both critical scattering and phase separation can be made to occur, due solely to the small but finite thermodynamic differences between protonated and deuterated molecules. These experiments helpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 76 publications
0
19
0
Order By: Relevance
“…21,22,42 In prior studies it was also demonstrated that there is an isotope effect contribution to the interaction parameter between labeled and unlabeled molecules. 38,43,44 However, for the broad copolymers of interest in the present study, the main contribution to the phase structure of the melt, i.e, whether the melt separates into two or more distinct phases, is the variance of the interchain distribution of branching content and the molecular weight, as first described by Scott 45 and later applied by Crist et al 46 to predict the stability condition of a compositionally heterogeneous linear low density polyethylene.…”
Section: ■ Experimental Sectionmentioning
confidence: 84%
See 1 more Smart Citation
“…21,22,42 In prior studies it was also demonstrated that there is an isotope effect contribution to the interaction parameter between labeled and unlabeled molecules. 38,43,44 However, for the broad copolymers of interest in the present study, the main contribution to the phase structure of the melt, i.e, whether the melt separates into two or more distinct phases, is the variance of the interchain distribution of branching content and the molecular weight, as first described by Scott 45 and later applied by Crist et al 46 to predict the stability condition of a compositionally heterogeneous linear low density polyethylene.…”
Section: ■ Experimental Sectionmentioning
confidence: 84%
“…Polyethylene and random copolymer blends that are phase separated due to the temperature effect or the effect of branching content on the interaction parameter may be analyzed on the basis of the ideal two-phase model, and the Porod’s law prediction that at large Q the coherent scattering intensity I ( Q ) should decrease proportionally to Q –4 . Past SANS experiments from our group on binary blends were carried out at only one melt temperature. ,,, Systematic analyses of SANS data as a function of melt temperature were undertaken by others in binary blends of model ethylene–1-butene copolymers to extract the dependence of the Flory–Huggins interaction parameter (χ) on temperature, composition, and chain length. ,, In prior studies it was also demonstrated that there is an isotope effect contribution to the interaction parameter between labeled and unlabeled molecules. ,, However, for the broad copolymers of interest in the present study, the main contribution to the phase structure of the melt, i.e, whether the melt separates into two or more distinct phases, is the variance of the interchain distribution of branching content and the molecular weight, as first described by Scott and later applied by Crist et al to predict the stability condition of a compositionally heterogeneous linear low density polyethylene.…”
Section: Methodsmentioning
confidence: 99%
“…This approach usually requires that one of the polymers be deuterated, which adds great expense unless one relies on a national user facility to support material synthesis. It should be noted that although deuterated compounds are commonly considered chemically identical to their nondeuterated counterparts, isotope effects (though small) have been seen to cause phase separation in polymer blends with small χ . Neutrons are generated by nuclear reactors, which severely limits accessibility.…”
Section: Polymer Blend Backgroundmentioning
confidence: 99%
“…It should be noted that although deuterated compounds are commonly considered chemically identical to their nondeuterated counterparts, isotope effects (though small) have been seen to cause phase separation in polymer blends with small χ. 90 Neutrons are generated by nuclear reactors, which severely limits accessibility. So, while it is the gold standard, it can only be applied to select systems with a compelling motivation to do so.…”
Section: ■ Polymer Blend Backgroundmentioning
confidence: 99%
“…[19][20][21] Similarly, mixtures of HDPE and LLDPE are homogeneous in the melt 4 when the branch content is low (i.e., <4 branches/100 backbone carbons). However, when the branch content is high (>8 branches/100 backbone carbons), the blends phase separate.…”
Section: Introductionmentioning
confidence: 98%